Processes of tourism space formation - Włodarczyk, Bogdan (Turyzm/Tourism, 2012)
The article is an attempt to name and define the processes which transform geographical space and result in the appearance or disappearance of tourism space as broadly understood. The processes include restructurization (modernization and revitalization) and degradation. All of them have been discussed in the context of their actual stage of tourism space development. More attention is devoted to degradation, which has only recently been seen as a process which may lead to the creation of spaces attractive to tourists.